DNA and Polyphosphate in Directed Proteolysis for DNA Replication Control - Ropelewska, Malgorzata; Gross, Marta H.; Konieczny, Igor (Frontiers in Microbiology, 2020)
The strict control of bacterial cell proliferation by proteolysis is vital to coordinate cell cycle processes and to adapt to environmental changes. ATP-dependent proteases of the AAA+ family are molecular machineries which contribute to cellular proteostasis. Their activity is important to control the level of various proteins, including those that are essential for the regulation of DNA replication. Since the process of proteolysis is irreversible, the protease activity must be tightly regulated and directed toward specific substrate at exact time and space in a cell. In our minireview, we discuss the impact of phosphate-containing molecules like DNA and inorganic polyphosphate (PolyP), accumulated during stress, on protease activities. We describe how the directed proteolysis of essential replication proteins contributes to the regulation of DNA replication under normal and stress conditions in bacteria.